Linguistic landscape in Malaysia: The case of language choice used in signboards - Mansoor, Siti Salwah; Hamzah, Nurul Huda; Shangeetha, R.K. (Universitas Syiah Kuala, 2023)
This study aimed to investigate the languages used in shop signs in three different areas in Semenyih, Selangor, Malaysia. Using a mixed-method approach, this paper identified the preferred language for shop signs in the town of Semenyih, Pelangi Semenyih, and Setia Ecohill, as well as examined the relationship between the language choice in signages and linguistic landscape in Malaysia. A total of 180 signboards was photographed to ensure the impartiality of data collection, and they were coded based on four aspects: full names of the shops in various languages, the business scope of the shops, the number of languages used in shop signs, size of the scripts, and layout of languages highlighted, adopted from the study of Shang and Guo (2017). Questionnaires and interviews with the shop owners were also employed to elicit information about their preferences regarding the language choice for their shop signages, which shed light on the impact of the development in Semenyih towards the choice of shop signages. The findings revealed that, despite the regulations imposed by the local city council (Majlis Perbandaran Kajang (MPKJ) or Kajang Municipal Town Council) on the permissible shop signages, the shop owners still used languages other than the Malay language in their signboards, such as English, Mandarin, and Tamil, with English being the most dominant one. This indicates that, as the towns develop, the linguistic landscape here changes with importance being given to signboards in English compared to Malay.